Population pharmacokinetic/pharmacodynamic modelling of eltrombopag in healthy volunteers and subjects with chronic liver disease. (March 2014) - Farrell, Colm; Hayes, Siobhan C.; Wire, Mary; Zhang, Jianping
<x xml:space="preserve">Abstract</x> Aims To characterize the pharmacokinetics (PK)/pharmacodynamics (PD) of eltrombopag in chronic liver disease (CLD). Methods The PK/PD model was developed using data from 79 CLD patients using nonlinear mixed‐effects modelling. Results The PK of eltrombopag were described by a two‐compartment model with dual sequential first‐order absorption. Gender, race and severity of CLD were predictors of the apparent clearance of eltrombopag. The PD of eltrombopag in CLD were adequately described by a four‐compartment lifespan model, in which eltrombopag stimulated platelet precursor production rate. East Asian CLD patients were less sensitive to the stimulatory effect of eltrombopag. Following a daily dose regimen of 50 mg eltrombopag, the time to achieve peak platelet counts was longer for the CLD population compared with patients who had immune thrombocytopenic purpura, but was comparable to patients with hepatitis C. Likewise, it took a longer time for platelet counts to rebound back to baseline once eltrombopag treatment was discontinued. Conclusions The time course of the platelet response in CLD was different from that in immune thrombocytopenic purpura but comparable to that in hepatitis C.